(untitled) (Bangladesh Journal of Botany, 2020)
Experiments were carried out to produce chitosan from a locally available mushroom and to use the produced chitosan as a matrix to immobilize α-amylase. On the basis of morphological characteristics and the sequence of the internal transcribed spacer region of the nuclear rDNA, the fungal sample was identified as Pleurotus ostreatus. The average crude chitin content in the dried fruit body of P. ostreatus was 24.11%. The average yield of chitosan from P. ostreatus was 163.3 mg/g dry weight and the degree of deacetylation of the produced chitosan was 73.42%. This chitosan was used as a matrix to immobilize α-amylase. The diameter of the α-amylase immobilized beads ranged from 1839 - 2273 μm. The amount of reducing sugar produced from starch by using free α-amylase and chitosan-immobilized α-amylase was 1.710 and 1.508 mg/ml, respectively. Immobilized enzyme produced only 11.81% less reducing sugar than that of the soluble enzyme in the first cycle. However, immobilized α-amylase was easily recovered from the product and reused for two more cycles which was not possible with the same soluble free enzyme. Considering the total production of reducing sugar in three cycles, chitosan-immobilized α-amylase was found to be more productive and cost-effective than conventional soluble enzymatic reaction.